2012
DOI: 10.1007/s00414-012-0738-y
|View full text |Cite
|
Sign up to set email alerts
|

Postmortem biochemical investigations in hypothermia fatalities

Abstract: Despite the progress made during the past several decades in forensic pathology, the possibilities for the postmortem diagnosis of hypothermia remains relatively limited. Aside from histology and immunohistochemistry, numerous authors have investigated the postmortem biochemistry of hypothermia fatalities. Several biochemical markers (e.g., glucose, electrolytes, hormones, ketone bodies, and neurotransmitters) and various biological samples (e.g., blood, urine, heart, liver, skeletal muscle as well as pericard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 68 publications
0
28
0
1
Order By: Relevance
“…Several histologic findings associated with hypothermia fatalities have been described in medicolegal literature including depletion of hepatic glycogen, fatty degeneration of the renal tubular epithelium (subnuclear vacuolization of renal tubular epithelial cells or Armanni-Ebstein phenomenon), pancreatic changes (focal necrosis of pancreatic and peripancreatic adipose tissue, hemorrhagic and nonhemorrhagic pancreatitis, adenocyte vacuolation), vacuolization of anterior pituitary gland cells, hepatocytes, adrenal cells and renal cells, hypoxic cardiac changes as well as fatty changes of cardiac myocytes and hepatocytes. A strong correlation among frost erythema, Wischnewski spots, and basal vacuolization of renal tubular epithelial cells has been observed by some authors who postulated that the Armanni-Ebstein phenomenon might be considered the most "indicative" histological finding of hypothermia fatalities [7,9,13,[23][24][25][26][27][28].…”
Section: Microscopic Findingsmentioning
confidence: 88%
See 3 more Smart Citations
“…Several histologic findings associated with hypothermia fatalities have been described in medicolegal literature including depletion of hepatic glycogen, fatty degeneration of the renal tubular epithelium (subnuclear vacuolization of renal tubular epithelial cells or Armanni-Ebstein phenomenon), pancreatic changes (focal necrosis of pancreatic and peripancreatic adipose tissue, hemorrhagic and nonhemorrhagic pancreatitis, adenocyte vacuolation), vacuolization of anterior pituitary gland cells, hepatocytes, adrenal cells and renal cells, hypoxic cardiac changes as well as fatty changes of cardiac myocytes and hepatocytes. A strong correlation among frost erythema, Wischnewski spots, and basal vacuolization of renal tubular epithelial cells has been observed by some authors who postulated that the Armanni-Ebstein phenomenon might be considered the most "indicative" histological finding of hypothermia fatalities [7,9,13,[23][24][25][26][27][28].…”
Section: Microscopic Findingsmentioning
confidence: 88%
“…These include the lungs, myocardium, anterior pituitary gland, adrenal medulla, hypothalamus, midbrain periaqueductal gray matter, renal tubular epithelium, distal and collecting renal tubules, glomerular podocytes, brain parietal lobe, hippocampus, and cerebral cortex, with extremely promising results in some cases. However, immunohistochemistry has still not provided significantly reliable diagnostic criteria for the postmortem diagnosis of hypothermia [24,[28][29][30][31][32][33].…”
Section: Microscopic Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many different biochemical substances and sample types have been studied in order to find an indicator of ante-mortem hypothermia or cold exposure [20]. After analysing several proposed markers in hypothermia deaths, Palmiere et al [21] concluded that the best indicators of hypothermia are increased levels of ketones and isopropyl alcohol in blood, adrenaline in urine, and cortisol in serum and urine.…”
Section: Discussionmentioning
confidence: 99%